Formation of Functional Silicon Nitride Layers by Selective Plasmochemical Etching - V. V. Emelyanov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
At present, with the development of nanotechnology, plasma-chemical etching remains practically the only tool for transferring an integrated circuit pattern in a masking layer to a substrate material due to the fact that the pattern transfer accuracy is comparable to the size of etching gas ions. Requirements for plasma technology: permissible defects, selectivity (material selectivity), line width control, etching uniformity are becoming more stringent and, as a consequence, more difficult to implement. To increase the rate and selectivity of plasma-chemical etching of silicon nitride films during plasma processing of a gas mixture consisting of both a fluorine-containing gas and oxygen, sulfur hexafluoride with a concentration of 70–91 vol.% was used as a fluorine-containing gas with an oxygen concentration of 9–30 vol.%.